The Influence Of Tourism Attraction, Facilities And Digital Promotion On The Interest In Visiting Pagar Alam City Tourism Village - Ahmad Feriyansyah; M. Yani Syafei; Umi Narimawati (UNIVED Press, 2024)
Tourism is an asset owned by a region to increase income and the economy of the community. To maximize the existing potential, it requires a strategy that can increase the interest of tourists visiting Pagar Alma. The attractiveness of tourist villages must be developed, so as to attract consumers to visit. Pagar Alam City has a natural tourism village and cultural tourism in South Sumatra, so it is necessary to conduct an analysis to determine the influence of tourist attraction, facilities and promotion on interest in visiting the tourist village of Pagar Alam city. This research data uses simple random sampling with instruments given to 100 tourists, consisting of local, archipelago, and foreign tourists visiting Pagar Alam City. Variable Attraction (average X1 : 0.803) and Facility variables (average X2 : 0.833) and Digital Promotion (X3 : 0.915) with the Partial Least Squeres method.